Exploring Hemingway's Depiction of War Violence: Psychological and Societal Impacts in Selected Novels - Emad Mohammad Abbar (Universitas Muhammadiyah Sidoarjo, 2024)
This study delves into the portrayal of war violence in four seminal novels by Ernest Hemingway, namely,